Strategic alliances for innovation and R & D - Das, T. K. 1938- (Emerald Publishing Limited : Information Age Publishing, Inc., 2014)
Strategic Alliances for Innovation and R&D is a volume in the book series Research in Strategic Alliances that focuses on providing a robust and comprehensive forum for new scholarship in the field of strategic alliances. In particular, the books in the series cover new views of interdisciplinary theoretical frameworks and models, significant practical problems of alliance organization and management, and emerging areas of inquiry. The series also includes comprehensive empirical studies of selected segments of business, economic, industrial, government, and non-profit activities with wide prevalence of strategic alliances. Through the ongoing release of focused topical titles, this book series seeks to disseminate theoretical insights and practical management information that should enable interested professionals to gain a rigorous and comprehensive understanding of the field of strategic alliances.Strategic Alliances for Innovation and R&D contains contributions by leading scholars in the field of strategic alliance research. The 11 chapters in this volume cover a number of significant topics that encompass innovation and R&D through strategic alliances. The chapter topics cover both the broader issues, such as the governance of high-tech alliances, knowledge flows in innovation clusters, co-innovation, and incomplete contracting, and the more focused problems of inexperienced firms in R&D consortia, new product development, and managing alliance portfolio evolution in service innovation. The chapters include empirical as well as conceptual treatments of the selected topics, and collectively present a wide-ranging review of the noteworthy research perspectives on the role of strategic alliances in the pursuit of innovation and R&D.
Keywords: Strategic alliances (Business); Research, Industrial.; Technological innovations.; New products.; Business & Economics -- Marketing -- Research.; Business innovation.; Market research.; elektronické knihy; electronic books